Space traffic management system: Challenges and prospects - (:unkn) unknown (IEEE, 2007)
Space is a huge but not unlimited resource. Space around the Earth is getting more and more crowded because of the increasing number of space objects and the limited availability of prime orbital locations. As a result, operations in space as well as getting there and back require more sophistication and international, coordination. Everything traveling in space and all the channels on electromagnetic spectrum used to reach space make up the elements of Space Traffic. The paper makes the case for a Space Traffic Management System (STMS) and proposes a reference model for STMS. The proposed STMS performs five main services: Space Monitoring & Tracking Service, Space Data Management Service, Space Operation Service, Space Warning Service and Space Conflict Management Service. The paper elaborates and explains these services, taking into consideration the political and especially technical challenges together with pertinent international law, regulations and accepted practice.